On the singular integral equations approach to the interface crack problem for piezoelectric materials (Archives of Mechanics - Test, 2000)
A plane strain problem for an interface crack with poling axis orthogonal to the crack plane is considered. The contact zone model with an artificial contact zone is considered for electrically permeable crack. By means of the method of singular integral equations, the quasi-invariance of the energy release rate with respect to the contact zone length is demonstrated. The appearance of a singularity of real power type instead of an oscillating singularity for insulated crack faces for most combinations of ceramics is shown. In a numerical way, the comparison of stresses and electrical displacements corresponding to the different interface crack models is employed.